Antihypertensive Activities of Peronema Canescens Jack Extract: An In Vivo Study - Ma'ruf, Muhammad; Bachri, Moch Saiful; Laela Hayu Nurani, (Scripta Medica, 2025)
Background/Aim: Hypertension commonly known as high blood pressure is characterised by a systolic readings of 140 mm Hg or higher and/or a diastolic readings of 90 mm Hg or above. Elevated blood pressure can lead to a heightened release of nitric oxide, a crucial factor in vascular relaxation. Peronema canescens Jack, commonly referred to as Sungkai, is known to contain flavonoids with antihypertensive properties and antioxidants that may help prevent cellular oxidation. This research aimed to evaluate the antihypertensive effects of ethanol extract from Peronema canescens Jack leaves and its impact on nitric oxide levels in hypertensive rats.Methods: This study used hypertensive male Wistar rats induced by NaCl (3.75 g/kg BW) and prednisone (1.5 mg/kg BW) administered orally. Blood pressure measurements were conducted using the non-invasive tail-cuff method and nitric oxide levels were analysed by reacting the sample with the Griess Reagent Assay.Results: The study's findings demonstrated a decrease in systolic, diastolic and mean arterial blood pressure, along with an increase in nitric oxide levels after administering ethanol extract of Peronema canescens Jack leaves (EEPC) at dosages of 50, 100 and 200 mg/kg BW. The most significant reduction in blood pressure was noted at the 100 and 200 mg/kg BW dosages (p < 0.05), while the highest elevation in nitric oxide levels was observed at the 200 mg/kg BW dosage (p < 0.05).Conclusion: The study concludes that administering the EEPC to hypertensive rats, induced by NaCl and prednisone, can lower blood pressure and elevate nitric oxide levels. These findings suggest that Peronema canescens Jack leaves hold potential as an antihypertensive agent.